The Stability of Party Power in Turkey after President Erdogan’s Victory in the 2023 Elections - Ibrahim, Sarah Farhan; Jawhar, Alaa Mohammed (Journal of Ecohumanism, 2024)
The present research aims to identify the impact of Erdogan’s victory on the basic budgets in Turkey and its impact on the opposition parties and the strength of the opposition, as well as on the Turkish economy, as the economic factor played a significant and influential role in the results of the Turkish elections, which led to the rise of the Justice and Development Party with Erdogan’s victory. This party has an effect on the political and democratic process in the country. Thus, the investigation includes two axes: the first, political parties in Turkey, and the second, the Turkish elections in 2023 AD.